The Influence Of Perception Of Convenience, Perception Of Risk And Financial Technology On Interest In Using Paylater Among Students - Niken Tiya Rahmadan; Yulpa Rabeta (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of Perceived Ease of Use, Perceived Risk, and Financial Technology on the intention to use PayLater services among university students in Lubuklinggau. The population included students from universities in Lubuk Linggau city, with a sample of 100 respondents selected using purposive sampling. Data were analyzed using Partial Least Square (PLS) with SmartPLS to test the relationships among constructs, allowing for both partial and simultaneous effect assessments. The results indicate that Perceived Ease of Use and Perceived Risk do not have a significant direct effect on the intention to use PayLater, whereas Financial Technology has a strong positive and significant effect with a path coefficient of 0.830 and T-statistic of 8.084. Simultaneously, the three independent variables significantly influence the intention to use PayLater, with a coefficient of 0.364 and P-Value of 0.000. The R-Square value of 0.456 suggests that 45.6% of the variance in usage intention is explained by the model, while the remaining is influenced by other external factors. Further analysis highlights the importance of financial literacy, prior platform experience, social factors, hedonic motivation, and perceived behavioral control as contextual determinants of PayLater adoption decisions. In conclusion, financial technology innovation emerges as the dominant factor driving PayLater usage intention, while Perceived Ease of Use and Perceived Risk require mediation or moderation approaches to fully understand their influence, providing practical implications for platform development and user education.